International Student Agency in Emergency: Insights from Government-funded Students from Kazakhstan - Kuzhabekova, Aliya; Amankulova, Zhuldyz (Journal of International Students, 2024)
This qualitative study uses data from interviews with 20 recipients of a Kazakhstani “Bolashak” scholarship to explore how international students overcome structural barriers and manifest agency in the conditions of public health emergency.  The analysis addresses the gap in the scholarly literature on agency of international students by explicitly focusing on manifestations of agency in the experiences of students from Kazakhstan, who have not yet received sufficient attention in research, and by following the students in a variety of country destinations. In addition, in contrast to the majority of studies conducted in the past, instead of recruiting students on a campus of a specific university or in the context of a single country, this study recruits participants from among recipients of a government-sponsored scholarship. The findings are interpreted with the help of Relational Ecological Theory of Agency.